Morphological transformations in rat thymus under influence of multiplegravitational overloads and after pharmaceutical correction - Moroz G.A. (Морфологія, 2012)
Using light and transmission electron microscopy techniques morphological features of mature male Wistar rats, which were exposed to hypergravity (9 g, 10 minutes, daily, 45times), were investigated. It was revealed, that reaction of thymus on multiple hypergravity resulted in haemodynamic changes and involution of lymphoid tissue according to the adaptive and compensatory reaction of the organ under repeated stress action. Administration of glutargin as an adaptogen under systematic hypergravity overloads provides certain corrective effect. Hypergravity-induced involution changes neither progress, nor totally arrest.